Encyclopedia of Life Sciences 2016
DOI: 10.1002/9780470015902.a0002335.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Roots: Contribution to the Rhizosphere

Abstract: Diverse compounds exuded by different parts of the root system create a unique environment known as the rhizosphere. Interactions among microorganisms found within the rhizosphere and communication between these microorganisms and plant roots play an important role in maintaining plant health. In 2004, the discovery of deoxyribonucleic acid (DNA)‐based neutrophil extracellular traps (NETs) have transformed our understanding of mammalian immune responses. Subsequent studies revealed that plant roots express a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…RBCs and mucilages have been shown to protect root tips from chemical and biological stresses, such as iron toxicity (Xing et al, 2008) and fungal infection (Hawes et al, 2000; Gunawardena and Hawes, 2002). Previous reports showed that the presence of RBCs and mucilages decreases Al accumulation and increases Al tolerance (Barcelo and Poschenrieder, 2002; Curlango-Rivera et al, 2016; Hawes et al, 2016). Al-resistant plants tend to have less Al accumulation than do Al-sensitive plants (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…RBCs and mucilages have been shown to protect root tips from chemical and biological stresses, such as iron toxicity (Xing et al, 2008) and fungal infection (Hawes et al, 2000; Gunawardena and Hawes, 2002). Previous reports showed that the presence of RBCs and mucilages decreases Al accumulation and increases Al tolerance (Barcelo and Poschenrieder, 2002; Curlango-Rivera et al, 2016; Hawes et al, 2016). Al-resistant plants tend to have less Al accumulation than do Al-sensitive plants (Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…77Bb1, some genes for plant growth hormones (brassinosteroid, flavone, flavonol, flavonoid, isoflavonoid, isoquinoline, phenylpropanoid, stilbenoid, diarylheptanoid, gingerol, tropane, piperidine, pyridine alkaloid, and zeatin) and antibiotics (novobiocin, penicillin, cephalosporin, puromycin, streptomycin, and tetracycline) were found. This indicates the ability of this bacterium to influence plant growth and development by increasing its ability to survive in a given environment [56,58]. Genes encoding aldehyde dehydrogenase, nitrilotriacetate monooxygenase (components A and B), 3-hydroxyacyl-CoA dehydrogenase, enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase, acyl-CoA synthetase, flavodoxin reductases, and probable poly(beta-D-mannuronate) O-acetylase, present in genome of Achromobacter sp.…”
Section: Analysis Of Genes Taking Part In Biosynthesis Of Secondary M...mentioning
confidence: 99%